(3GdGSJLhGH chSjdI ef hSGFd GdQbGHI Ydi CYeGd GdSdWI GdJfajPjI (B:s (3OQGSI ebGQfI aj OSGJjQ HdOGf eLdS GdJYGhf GdNdjLj (B/s - (3GdbejT, CMeO efUhQs ((3HjQhJ (B:s (3efThQGJ GdMdHj GdMbhbjI,s, 2012)
(3aj gPG GdcJGH jYQV GdeDda eSCdI GdGSJLhGH aj EWGQ ebGQf jJMOO fWGbg HOSGJjQ Ohd eLdS GdJYGhf GdNdjLj, fXQG dJTGHggG ef MjK fXe GdMce CNPG HGdfXGe Gdedcj GdhQGKj hMOGKI YgOgG HGdMjGI GdOSJhQjI, eeG jLYd ef GdVQhQj GdESgGe aj OQGSI GdYOjO ef GdeSGFd GdJj dG JRGd JMX HGgJeGe cGa ef bHd GdHGMKjf aj abg GdbGfhf GdYGe, hefgG GdGSJLhGH, hJchf GdcJGH ef aUdjf eJJGdjjf eSHhbjf HeHMK JegjOj ceG jdj (B: (3eHMK JegjOj (B: (3acQI GdGSJLhGH, GdaUd GdChd (B: (3GdGSJLhGH aj MGd GdSchf, GdaUd GdKGfj (B: (3GdGSJLhGH aj MGd GdMQcI(B.s
(3HHdjhLQGajI (B: (3UaMI (B283-292.s
Keywords: (3eLdS GdJYGhf dOhd GdNdjL GdYQHjIs; (3GdOSGJjQs -- (3Ohd GdNdjL GdYQHjIs; (3GdSdWI GdJfajPjIs -- (3bhGfjf hJTQjYGJs -- (3Ohd GdNdjL GdYQHjIs